Кон Arnaud Tomès, Le sujet: Për Arnaud Tomès, Le sujet - Sekulovski, Jordančo; Ahmeti, Xhabir (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Jordančo Sekulovski | Јорданчо Секуловски Title (Macedonian): Кон Arnaud Tomès, Le sujet Title (Albanian): Për Arnaud Tomès, Le sujet Translated by (Macedonian to Albanian): Xhabir Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 233-238 Page Count: 6 Citation (Macedonian): Јорданчо Секуловски, „Кон Arnaud Tomès, Le sujet“, Идентитети: списание за политика, род и култура, т. 6, бр. 1 (зима 2007): 233-238. Citation (Albanian): Jordančo Sekulovski, „Për Arnaud Tomès, Le sujet“, përkthim nga Maqedonishtja Xhabir Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007): 233-238.